Influence of filler wire and wire feed speed on metallurgical and mechanical properties of MIG welding–brazing of automotive galvanized steel/5754 aluminum alloy in a lap joint configuration. Issue 9 (February 2016) - Milani, Ali; Paidar, Moslem; Khodabandeh, Alireza; Nategh, Saeed
Abstract In this research, the galvanized steel with thickness of 2 mm was joined to the 5754 aluminum alloy with thickness of 3 mm by the cold metal transfer MIG welding–brazing process. The effect of the filler wires (AlSi3 Mn, AlSi5, and AlSi12 ) and wire feed speeds (4.7, 5, and 5.3 m/min) on metallurgical and mechanical properties have been discussed. According to the experimental results, thickness of intermetallic compound (IMC) layer which was formed along the interface during the MIG welding–brazing was varied by changing of parameters. In addition, the results indicated that by increasing of the wire feed speed, the thickness of IMC layer at first decreased and then increased. Results indicated that the maximum thickness variation of IMC layer belonged to the AlSi12 filler wire and the best consistent tensile strength was produced with AlSi3 Mn filler wire with an average value of 188 N/mm2 . Observation of the failed specimens indicated two types of failure modes under the tensile load, including the fractures occurred in HAZ of aluminum and the fractures occurred near IMC layer.